A Comparison of Ordered Categorical versus Discrete Choices within a Stated Preference Survey of Whole-Blood Donors. (April 2023) - Sadique, Zia; Cairns, John; De Corte, Kaat; Willis, Sarah; Miners, Alec; Bansback, Nick; Grieve, Richard
There are different stated preference (SP) approaches, including discrete choice experiments (DCEs). DCEs are a popular SP approach, but in some settings, alternative ways of framing survey questions may be more appropriate. The Health Economic Modelling Of Alternative Blood Donation Strategies (HEMO) study required choice tasks to be framed so that the study could estimate the effect of attribute levels on the frequency of a behavior—in this case, blood donation. SP questions were formulated to require ordered categorical responses from a single profile of attribute levels. However, it is unknown whether this way of framing SP questions leads to estimates of marginal rates of substitution (MRS) that are different from traditional DCE choices between 2 alternative profiles. The aim of this article is to compare estimates of relative preferences from SP questions requiring ordered categorical versus discrete choice responses. We compared relative preferences elicited from the 2 approaches for a common set of attributes and levels, formulated as choice tasks for 8, 933 whole-blood donors. We found that the 2 forms of survey questions provided similar MRSs estimates. For example, respondents were willing to trade off only a small increase in travel time to receive a health report, irrespective of whether the choice given was binary (DCE response; approximately 3 min) or from an ordered category (about 8 min). The finding that any differences in the estimated MRSs are not of substantive importance offers some reassurance for policy makers in that estimates of relative preference may be robust to alternative ways of framing the survey questions. These findings can encourage future studies to frame choice tasks that align with the study's objective. Highlights: This article compares the relative preferences from stated preference (SP) questions requiring ordered categorical versus discrete choice responses. The approaches were contrasted for blood donation service characteristics that offer opportunities to donate blood. The estimates of relative preferences for alternative blood donation service characteristics were similar between the 2 forms of SP approach. This study illustrates how SP survey questions can be formulated to provide responses on an ordered categorical scale and to estimate marginal rates of substitution between different attributes, which can be compared with those derived from discrete choice experiment (DCE) choices. The article highlights the potential value of considering alternative choice framings rather than relying solely on DCEs.